SOWING TERMS AND QUALITIES OF SOFT WINTER WHEAT - Yu. G. Skvortsova; E. V. Ionova (Зерновое хозяйство России, 2018)
The article considers the results of experiments dealing with effect of sowing terms and ancestors on sowing qualities of soft winter wheat on the sample of the variety ‘Don 107’. Soft winter wheat is one of the main food crops. The major task for farmers is to receive yield of high quality wheat. The primary factor in winter wheat cultivation is to choose an optimal term of sowing. As the quality of the yield largely depends on it, this issue is the most essential nowadays. Depending on sowing time and ancestors, seeds can get into the best of worst conditions, e.g. air and soil humidity, temperature regime. The beginning of development which influence a lot on bio chemical processes in seeds and plants, depends on sowing terms and ancestors, so the best sowing terms are greatly essential for receiving yields of better quality.  It has been determined that the maximum number of germs was received when the seeds grown after black fallow were sown on the 30 of September (91 p). When the seeds were sown on the 10 of September, they showed the minimum number of germs. The seeds grown after peas for grain gave the similar results.  On the autumn fallow the sowing term of the 30 of September gave the maximum field germination (87%), and the sowing term of the 10 of September gave the minimum of it (81%). The sowing term of the 30 of September gave the maximum field germination (83%) of seeds, sown after peas for grain. It has been established that on average the best sowing term for winter wheat in the Rostov region when the sowing quality of the crop increases after black fallow and peas for grain is the 30 of September.